Fracture toughness of TiAl-Cr-Nb-Mo alloys produced via centrifugal casting - A. Brotzu; F. Felli; D. Pilone (Fracture and Structural Integrity, 2012)
Fracture toughness of a TiAl base intermetallic alloy has been investigated at room temperature. The Ti-48Al-2.5Cr-0.5Nb-2Mo (at. %) alloy produced via centrifugal casting exhibits fine nearly lamellar microstructures, consisting mainly of fine lamellar grains, together with a very small quantity of residual beta phases along lamellar colony boundaries. In order to determine the alloy fracture toughness compact tension specimens were tested and the results were compared with those available in literature.